Problematika Guru dalam Menggunakan Media IT pada Pembelajaran Siswa Kelas 4 Sekolah Dasar - Sukartono; Salsabilla An’navi (Jayapangus Press, 2023)
Learning should take place in a fun way, where one of them uses IT learning media. Of the many teacher tasks in carrying out learning, the teacher also has problems, namely in using IT learning media. The purpose of this study was to analyze the teacher's problems in using IT media in the learning of 4th grade elementary school students. This study uses qualitative research with a phenonological approach. Data collection techniques through observation, interviews, and documentation. The subjects in this study were school principals, teachers and fourth grade students. Data analysis techniques use source triangulation and method triangulation. The results of the study show that the problems are in class management, the minimum number of media in schools, media storage, lack of teacher knowledge and skills and teachers' hassles when teaching using IT media. To improve teacher professionalism, schools carry out workshops using sparkol videoscribe media and are given motivation so that teachers are even more enthusiastic about applying learning media.